Medium y su aporte en el aprendizaje de los estudiantes de la Carrera de Pedagogía de las Ciencias Experimentales Informática, sección matutina de la Universidad Técnica de Babahoyo, Periodo Académico octubre 2024 - marzo 2025. - Bermeo Baquerizo, Kleber Alexis (2025)
The topic of this research work is Medium and its contribution to the learning of the students of the Pedagogy of Experimental Computer Sciences career, morning section of the Technical University of Babahoyo, academic period October 2024 - March 2025. The objective is to analyze the contribution of Medium to the learning of the students, the methodology by which the information was collected through virtual surveys to the students of the Pedagogy of Experimental Computer Sciences career through a question questionnaire, because for the collection of information, a one-time survey was used in which the students of the PCEI career participated: descriptive, because the knowledge about the variables of the Medium tool was deepened, in learning, the population investigated was three hundred and eighty-three and a sample of one hundred and ninety-two students of the PCEI career was determined. The results of this work were 80% of the students totally agree and agree with the contribution of Medium in learning and 20% of the selected respondents disagree with the contribution of the Medium tool. One of the conclusions was: the Medium tool is recommended for the publication of scientific articles, which allows generating new knowledge for the authors when using this technological tool.